Transforming River Water Quality Monitoring: An Advanced IoT and Sensor-Based - Zubaidah, Tien; Hamzani, Sulaiman; Legowo, Agung Cahyo (Al-Ard: Jurnal Teknik Lingkungan, 2024)
Background of this research is river water quality monitoring that crucial to maintaining the sustainability of river ecosystems. In this context, Internet of Things (IoT) technology and sensors have emerged as a promising solution to enhance monitoring efficiency and accuracy. Methodology: This article describes the implementation of IoT technology and sensors for water quality monitoring in the Martapura River, Banjar Regency, South Kalimantan. Water quality parameters such as pH, turbidity, conductivity, temperature, and dissolved oxygen were measured periodically during testing. The results of this research is the developed monitoring system demonstrated satisfactory results in measuring water quality parameters with low deviation and variation levels. Moreover, the System achieved a high uptime rate, even when facing challenges such as sensor errors, WiFi connection disruptions, and power outages. The implementation of IoT technology and sensors in river water quality monitoring has positively impacted monitoring efficiency, accuracy, and reliability. These results emphasize the significant potential of this technology in supporting river ecosystem conservation efforts in the region.